Controlled copolymerization of α-NCAs and α-NNTAs for preparing peptide/peptoid hybrid polymers with adjustable proteolysis. Issue 3 (15th December 2021) - Zou, Jingcheng; Zhou, Min; Ji, Zhemin; Xiao, Ximian; Wu, Yueming; Cui, Ruxin; Deng, Shuai; Liu, Runhui
Abstract : The living and controlled copolymerization of α-NCAs and α-NNTAs enables the facile synthesis of peptide/peptoid hybrid polymers with an alternating-like distribution of residues and adjustable proteolysis by varying the proportion of peptoid residues. Abstract : Peptides and polypeptides have excellent biocompatibility and numerous biological functions; however, their application is restricted by their proneness to proteolytic degradation. Although the incorporation of peptoid residues into peptides can improve their stability against proteases, the synthesis of peptide/peptoid hybrid oligomers suffers from the tedious and time consuming solid-phase synthesis process. Hereby, we report a living and controlled copolymerization of α-amino acid N -carboxyanhydrides (α-NCAs) and N -substituted α-amino acid N -thiocarboxyanhydrides (α-NNTAs) for the facile synthesis of peptide/peptoid hybrid polymers with an alternating-like distribution of residues, controllable molecular weight and narrow dispersity. Moreover, this polymerization strategy enables quick synthesis of peptide mimicking peptide/peptoid hybrid polymers with adjustable proteolysis by varying the proportion of peptoid residues. Our studies shed some light on the facile synthesis of peptide mimicking peptide/peptoid hybrid polymers with tunable proteolysis and open new avenues for preparing novel peptide mimics with tunable proteolysis and large structural diversity.